Serum from Jiao-Tai-Wan treated rats increases glucose consumption by 3T3-L1 adipocytes through AMPK pathway signaling. Issue 4 (5th April 2019) - Yuan, Lin; Tang, Peng; Li, Hui-Jiao; Hu, Na; Zhong, Xiao-Yu; Lin, Min; Sun, Yin-Qiang; Lu, Min; Lu, Xiong
Abstract : Type 2 diabetes (T2DM) is characterized by hyperglycemia resulting from insulin resistance. Jiao-Tai-Wan (JTW), a traditional Chinese medicine consisting of a 10:1 formulation of Rhizoma Coptidis (RC) and Cortex Cinnamomi (cinnamon) was shown to have hypoglycemic efficacy in a type 2 diabetic mouse model. Here we investigated whether glucose consumption by insulin-resistant adipocytes could be modulated by serum from JTW-treated rats, and if so, through what mechanism. JTW-medicated serum was prepared from rats following oral administration of JTW decoction twice a day for 4 days. Fully differentiated 3T3-L1 adipocytes – rendered insulin resistance by dexamethasone treatment – were cultured in medium containing JTW-medicated rat serum. JTW-medicated serum treatment increased glucose uptake, up-regulated levels of phosphorylated adenosine 5′-monophoshate-activated protein kinase (p-AMPK), and stimulated expression and translocation of glucose transporter 4 (GLUT4). JTW-medicated serum induced significantly greater up-regulation of p-AMPK and GLUT4 than either RC or cinnamon-medicated serum. JTW-medicated serum induced effects on 3T3-L1 adipocytes could be partially inhibited by treatment with the AMPK inhibitor compound C. In conclusion, JTW-medicated serum increased glucose consumption by IR adipocytes partially through the activation of the AMPK pathway, and JTW was more effective on glucose consumption than either RC or cinnamon alone.